(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2004)
Professors who teach how to teach (Experimental Analysis of Behavior - EAB - professors, for instance) should be the most effective professionals in the field of education. This does not seem to be true. To become so, Teaching should be faced in a scientific way. We should look for teaching practices that allow all professors to teach well and all students to learn as efficiently as their repertoires permit. EAB, a discipline that is highly dedicated to the comprehension and the teaching of learning processes, must follow its theories and procedures when the issue is the practice of teaching. Since 1964, we have a teaching methodology that reflects, in the practice, these theories: PSI (Personalized System of Instruction). The present paper discuss the PSI, trying to call behavior analysts’ attention to this efficient teaching methodology, in agreement with the behavior-analytic principlesweteach.